2020
DOI: 10.1039/d0fo01797c
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of alfalfa saponins on oxidative stress-induced apoptotic cells

Abstract: As it is known, alfalfa saponin can be used as a feed additive in the pig’s diet. And the addition of alfalfa saponin to the pig’s diet could improve animal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In this regard, plant extracts showed remarkable anti-inflammatory properties thanks to the presence of multiple molecules [66,75]. At the same time, other authors highlighted the anti-inflammatory actions of single molecules purified from plant extracts [5,36,38]. Further studies will be needed to evaluate whether the phytocomplex of GP shows a greater anti-inflammatory power than any single molecule present in the same phytocomplex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, plant extracts showed remarkable anti-inflammatory properties thanks to the presence of multiple molecules [66,75]. At the same time, other authors highlighted the anti-inflammatory actions of single molecules purified from plant extracts [5,36,38]. Further studies will be needed to evaluate whether the phytocomplex of GP shows a greater anti-inflammatory power than any single molecule present in the same phytocomplex.…”
Section: Discussionmentioning
confidence: 99%
“…Like all secondary metabolites produced by plants, the saponin content is also influenced by various biotic stimuli such as parasite attacks, pathogenic infections, the mutualistic symbiosis of plants with rhizobium bacteria and mycorrhizal fungi [35]. Saponins are functional components of many plant-based drugs and popular medicines and have shown an important function in improving the inflammatory, immune and anticancer response and in reducing cholesterol [36,37]. Furthermore, saponins showed good activity in cellular protection from ischemia and hypoxia [38].…”
Section: Saponinsmentioning
confidence: 99%
“…Concentration-dependent and time-dependent assays were conducted to determine the cell viability of cells decreased by about half after the treatment with 300 μmol/L H 2 O 2 for 24 h compared with the control group. The results indicated that the median lethal concentration of H 2 O 2 in IPEC-J2 cells was 300 μmol/L, which was higher than the median lethal concentration (150 μmol/L) of H 2 O 2 in IEC-6 cells, indicating IPEC-J2 cells were much more tolerant to H 2 O 2 than IEC-6 cells [ 16 ]. For the suitable concentration and appropriate time of IPEC-J2 oxidative stress stimulation, cells treated with 300 μmol/L H 2 O 2 for 24 h were determined as the oxidative stress model of this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal mucosal epithelial cells are important functional cells of the intestine which play a key role in digestive enzymes’ secretion, nutrients’ digestion, absorption, transport, stress response and immune barrier [ 14 , 15 ]. The previous study has shown the antioxidant effects of alfalfa saponins on rat intestinal epithelial cells (IEC-6 cell line) [ 16 ]. However, IEC-6 is a cell line from rat, one kind of model animal, whose digestive tube construction is very different from that of swine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are responsible for antidiabetic, anti-obesity, antioxidant, as well as many other biological activities. Other non-phenols such as the saponin component of alfalfa play key biological functions in the body [ 23 ]. Saponins and their derivatives such as prosapogenins and sapogenins have been reported to exert a high antimicrobial activity against yeasts and bacterial strains [ 24 ].…”
Section: Phytochemicals In Selected Edible Plant Sproutsmentioning
confidence: 99%